Response of Sorghum Genotypes to Different Water Levels Created by Sprinkler Irrigation - Ibrahim, Yassin M (Annals of Arid Zone, 2016)
Eight sorghum genotypes were subjected to different levels of water stress through line source sprinkler, in field experiments on a loamy sand soil in AI-Ain, UAE. Grain and forage yields were significantly reduced by moisture stress. Grain sorghum genotypes had significantly higher grain yield than others, with Feterita and Um Benin being the best in 1991 and 1992, respectively. Forage sorghum genotypes yielded significantly higher fodder with Pioneer being the best in both the seasons. Drought tolerance index showed significant differences between grain sorghum and fodder sorghum but the differences within each group were not significant. Water-use efficiency decreased with stress in all the genotypes in both the years. The study suggested that whenever water is limiting for production, the emphasis should be towards maximum economic production per unit of applied water rather than on maximum yield.